Comparative plasma metabolomics of Delta and Omicron SARS-CoV-2 variants: insights into variant-specific pathogenesis and therapeutic implications - Pimentel, Eric; Banoei, Mohammad Mehdi; Lee, Chel Hee; Winston, Brent W. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe emergence of SARS-CoV-2 led to a global pandemic. Delta and Omicron, classified as concerning variants, differ significantly in transmissibility, disease severity, and antibody neutralization. Delta is associated with more severe disease, whereas Omicron is linked to increased transmissibility yet milder disease. This study investigates plasma metabolomic differences between Delta and Omicron infections and their associations with disease severity and treatment response. Importantly, this work examines variant-specific treatment metabolic effects – an aspect that remains underexplored despite the ongoing evolution of SARS-CoV-2 variants – and thus begins to fill a critical gap in the literature.MethodsA total of 109 hospitalized SARS-CoV-2 patients, confirmed by RT-PCR positivity (53 Delta, 56 Omicron), were matched by age and sex. Plasma samples collected on hospitalization days 1, 2, and 7 were analyzed using DI/LC-MS/MS-based (direct injection, liquid chromatography-tandem mass-spectrometry) targeted metabolomics. We employed univariate and multivariate statistical and pathway analyses to investigate and characterize metabolomic differences.ResultsDistinct metabolic profiles differentiated Delta and Omicron infections. Specific metabolites, including tyrosine, asparagine, leucine, and acylcarnitines (C3, C4, C5), significantly distinguished variants and severity groups. Delta infections showed higher associations with severe outcomes. Corticosteroid treatment influenced metabolic profiles, revealing associations with modulation of metabolic and clinical responses.ConclusionThis study reveals significant plasma-based metabolic differences between Delta and Omicron SARS-CoV-2 variants, potentially reflecting their distinct clinical outcomes and severities.